2016
DOI: 10.3847/0004-637x/818/2/198
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Chemistry in Turbulent Astrophysical Media. Ii. Effect of the Redshift Zero Metagalactic Background

Abstract: We carry out direct numerical simulations of turbulent astrophysical media exposed to the redshift zero metagalactic background. The simulations assume solar composition and explicitly track ionizations, recombinations, and ion-by-ion radiative cooling for hydrogen, helium, carbon, nitrogen, oxygen, neon, sodium, magnesium, silicon, sulfur, calcium, and iron. Each run reaches a global steady state that not only depends on the ionization parameter, U, and mass-weighted average temperature, T MW , but also on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 76 publications
2
30
0
Order By: Relevance
“…To this end, we can turn again to the example presented in Figure 1. Gray et al (2015); Gray & Scannapieco (2016); Buie et al (2018) showed that at low amounts of turbulence, σ 3D 10 km s −1 (top panel), MAIHEM mass fractions agree well with the pure photoionization case computed with CLOUDY (Ferland et al 2013).…”
Section: Application To Cos-halos Datasupporting
confidence: 52%
See 1 more Smart Citation
“…To this end, we can turn again to the example presented in Figure 1. Gray et al (2015); Gray & Scannapieco (2016); Buie et al (2018) showed that at low amounts of turbulence, σ 3D 10 km s −1 (top panel), MAIHEM mass fractions agree well with the pure photoionization case computed with CLOUDY (Ferland et al 2013).…”
Section: Application To Cos-halos Datasupporting
confidence: 52%
“…Modifications for solving the hydrodynamic equations include using an unsplit solver based on Lee (2013) as well as a hybrid Riemann solver that utilizes the Harten Lax and van Leer (HLL) solver (Einfeldt et al 1991) to ensure stability in regions of strong shocks, and the Harten-Lax-van Leer-Contact (HLLC) solver (Toro et al 1994;Toro 1999) in continuous flows. MAIHEM was initially presented in Gray et al (2015) and further improved upon in Gray & Scannapieco (2016) and Gray & Scannapieco (2017).…”
Section: Maihem Modelsmentioning
confidence: 99%
“…3.3). (1) [13] 10 −6 -10 15 cm −3 1D 625 species (including atomic ions); CHIANTI, Stout, LAMDA databases no (9) DESPOTIC (2) [31] Cool atomic and molecular ISM 1D C, O, H, and He, plus a super-species M that represents a composite of metallic elements no (9) LIME (3) [26] 10 2 -10 12 cm −3 3D LAMDA database yes MAIHEM (4) [32], [65], [66] Has been tested at 0.4-1200 cm −3…”
Section: Tools For Solving Level Populations and Line Excitationmentioning
confidence: 99%
“…It is with these issues in mind that we carry out a set of numerical calculations of turbulent astrophysical media exposed to a radiation field with a blackbody spectral shape, making use of the atomic chemistry network discussed in Gray & Scannapieco (2016). Like in Gray & Scan-napieco (2016), we catalog the hydrodynamical and chemical properties, but unlike this previous work, we also compute the average line emission.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of turbulence on the steady state ionization fractions for several important astronomical elements has been studied both with (Gray & Scannapieco 2016) and without (Gray et al 2015) an ionizing UV background. In Gray et al (2015), we found that gas approximates a lognormal distribution with a variance that is well modeled, for supersonic turbulence, by…”
mentioning
confidence: 99%